Mach band sign: an optical illusion - Panikkath, Ragesh (Proc (Bayl Univ Med Cent), 2014)
The chest radiograph of a 63-year-old woman who was found unresponsive was concerning for pneumopericardium, but lacked the other corroborative features suggestive of pneumopericardium. None of the follow-up chest radiographs showed evidence of air around the heart. The radiolucent shadow that mimicked pneumopericardium in this case was due to an artifact known as Mach band sign, an illusion created by lateral inhibition in the light receptors in the retina.